2020
DOI: 10.1111/bju.15098
|View full text |Cite
|
Sign up to set email alerts
|

Management of benign prostatic hyperplasia in the 21st century: temporal trends in Australian population‐based data

Abstract: Objective To examine national trends in the medical and surgical treatment of benign prostatic hyperplasia (BPH) using Australian Medicare Benefits Schedule (MBS) and Pharmaceutical Benefits Scheme (PBS) population data from 2000 to 2018. Patients and methods Annual data was extracted from the MBS, PBS and Australian Institute of Health and Welfare databases for the years 2000–2018. Population‐adjusted rates of BPH procedures and medical therapies were calculated and compared in relation to age. Cost analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 40 publications
(49 reference statements)
2
33
1
Order By: Relevance
“…Greater understanding of these issues will facilitate planning to meet demand in primary care services given ongoing capacity shortage, and also secondary care as increased pharmacological treatment could be indicative of future demand for surgery. 23 Whether practices were NHS or GP-run, or had a dispensing pharmacy present within the GP practice, were associated with higher and lower prescribing volumes, respectively. While the individual characteristics of GP medical practices are known to differ by region 24 research accounting for these factors is relatively sparse; hence, it is unclear why this difference exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater understanding of these issues will facilitate planning to meet demand in primary care services given ongoing capacity shortage, and also secondary care as increased pharmacological treatment could be indicative of future demand for surgery. 23 Whether practices were NHS or GP-run, or had a dispensing pharmacy present within the GP practice, were associated with higher and lower prescribing volumes, respectively. While the individual characteristics of GP medical practices are known to differ by region 24 research accounting for these factors is relatively sparse; hence, it is unclear why this difference exists.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we have not investigated how differences in GP prescribing practices for BOO may impact on the rates of surgical management of this condition. For example, a study in Australia identified regional differences in the surgical management of BOO secondary to BPH 23 ; it would be interesting for future research to potentially link BPH prescribing practice with rates of surgical management of this condition. For example, it might be the case that medical therapy can delay the need for surgery by a number of years, or reduced rates of BPH prescribing in any particular Health Board may be associated with higher rates of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that some of these novel devices will stand the test of time, in contrast to the vast majority of their predecessors. Recent population-based data from Australia indeed suggest a more profound and prolonged diffusion of novel minimal invasive procedures [39]. Yet, one has to be aware that there are relevant discrepancies on the use of minimally invasive treatments for LUTS/BPH in various healthcare systems (even in well-developed countries), mainly due to differences in the reimbursement system.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmaceutical Benefits Schedule Item Reports were queried in May 2019, similar to methodology described previously [ 19 20 21 ]. Annual prescription data from 1992 to 2018, as well as monthly data from April 2014 (one year prior to the PBS changes) to April 2019 were collected for the item numbers listed for TRT, shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%